Protein concentrate obtainment from leaves and aerial part cassava (ManihotesculentaCrantz) Obtenção de concentrado protéico de folhas e parte aérea da mandioca (ManihotesculentaCrantz) - Janaina Lima da Silva; Simone Damasceno Gomes; Silvia Renata Machado Coelho; Janete Evarini; Priscila Ferri; Marney Pascoli Cereda; Shaiane Dal`Maso Lucas (Semina: Ciências Agrárias, 2012)
The aerial parts of cassava, constituted by leaves, stalk sand stems, are considered as agro-industrial waste, so, they are thrown away during roots crop. This material has content of protein, vitamin and mineral; therefore, it can be used as a dietary supplement for food industries. Thus, alternatives have come to extract protein from leaves and remove toxic agent sand anti-nutrients that make part of their composition. In this context, this study aimed at evaluating yield, mineral composition and functional properties of protein concentrates from leaves and aerial part of cassava. During the extraction of proteins, the following tested methods were:(1) isoelectric precipitation; (2) natural fermentation for five days; (3) fermentation for 48 hours and (4) fermentation for 48 hours, followed by pH adjustment. A 2 x 4 factorial design was used, the studied factors were the products (leaves and shoots) and the method of protein extraction (four methods), with three replications. From the results, it was observed that Method1 provided the highest yields of protein concentrate and protein extraction for cassava leaves, however, there was no significant difference among the extraction methods for the aerial part of cassava. The values of Fe, Mn and Zn increased in protein concentrates obtained both in leaves and the aerial part of cassava, especially for Method 3. The capacities of absorbing water and oil from protein concentrates were considered high for the four studied methods, thus, indicating a good application in food products. As partes aéreas da mandioca, representadas pelas folhas, hastes e caules, constituem-se como resíduos agroindustriais por serem desperdiçadas na colheita das raízes. Esse material possui valor protéico, vitaminas e mineiras, propiciando sua utilização como suplemento alimentar nas indústrias alimentícias. Alternativas neste sentido surgem para extrair a proteína das folhas e eliminar os agentes tóxicos e antinutricionais naturalmente presentes em sua composição. Neste contexto, o objetivo desta pesquisa foi avaliar rendimento, composição mineral e propriedades funcionais de concentrados protéicos, obtidos de folhas e parte aérea de mandioca. Na extração das proteínas, foram testados os métodos de (1) Precipitação Isoelétrica, (2) Fermentação Natural por 5 dias, (3) Fermentação por 48 horas e (4) Fermentação por 48 horas, seguida de ajuste de pH. Foi utilizado o delineamento fatorial 2x4, sendo os fatores o tipo de material (folhas e parte aérea) e o método de extração de proteína (quatro métodos), com três repetições. O Método 1 proporcionou os maiores rendimentos de concentrado protéico e extração de proteína das folhas de mandioca, porém, não foi verificada diferença significativa entre os métodos de extração para a parte aérea da mandioca. Os teores de Fe, Mn e Zn aumentaram nos concentrados protéicos da parte aérea da mandioca, com destaque para o Método 3. As capacidades de absorção de água e de óleo dos concentrados protéicos foram elevadas para os quatro métodos avaliados, indicando boa aplicação em produtos alimentícios.